DERMATOLOGY LIFE QUALITY INDEX IN PATIENTS OF PSORIASIS AND ITS CORRELATION WITH SEVERITY OF DISEASE - Khan, Jauhar Mumtaz; Rathore, Muhammad Usman; Tahir, Moizza; Abbasi, Tariq (Journal of Ayub Medical College Abbottabad, 2020)
Background: Patient suffering from psoriasis can be severely affected in their day to day activities and it may also result in reduced work efficiency and absenteeism from work leading to financial burden on the patient's family. This study was conducted using Dermatology Life Quality Index to assess the quality of life of a patient suffering from psoriasis being treated at a military hospital. Methods: This cross-sectional study was conducted in the outpatient unit of Department of Dermatology, Combined Military Hospital Abbottabad from 1st October 2013 to 31stJune 2014. The demographic data and Dermatology Life Quality Index of patients of psoriasis were recorded using a standard questionnaire and their final score was calculated to assess the effect of disease on patient's life. Extent/ severity of disease was assessed according to the body surface area involved. The data was analysed using SPSS-18. Mean and SD for numerical variables and frequencies and percentages for categorical were calculated. Results: A total of 160 patients fulfilling the inclusion criteria were included in the study. Mean age of the patients was 40.48 years (±12.58 years) with minimum age of 18 years and maximum of 74 years. 118 patients were males were (73.8%) and 42 were females (26.2%). Twenty (12.5%) patients had no effect on their life by the disease while 5 (3.1%) had extremely large effect. Most patients, i.e., 68 (42.5%) had moderate effect on their lives. 69 patients had mild psoriasis as per body surface area involved, 70 had moderate disease and 21 had severe disease. Conclusion: Psoriasis affects quality of life of patients not only physically but also psychologically and financially even when patients are under treatment. Psychological aspects also need to be addressed while treating the physical morbidity. Keywords: Psoriasis; quality of life; Social; Dermatology Life Quality Index; body surface area